2018
DOI: 10.11604/pamj.2018.30.85.12722
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and current modern contraceptive use among married women in Uganda: a cross-sectional study

Abstract: IntroductionThis paper examined the relationship between Intimate Partner Violence (IPV) and current modern contraceptive use (MCU) among married women in Uganda.MethodsWe used the 2011 Uganda Demographic and Health Survey (UDHS) data, selecting a weighted sample of 1,307 married women from the domestic violence module. Chi-squared tests and multivariate complementary log-log (clog-log) regressions were used to examine the relationship between IPV and current MCU, controlling for women's socio-demographic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…Vyas and Jansen, [16] Physical and sexual partner violence Individual-level, women's non-partner violence (sexual abuse by non-partner and witnessing violence in childhood. [16] The findings support the assertions of violence associated with women's prior/additional abuse and men's harmful masculinity expression [16] Wandera et al, [43]…”
Section: Study Outcome Variable Explanatory Variablessupporting
confidence: 73%
See 2 more Smart Citations
“…Vyas and Jansen, [16] Physical and sexual partner violence Individual-level, women's non-partner violence (sexual abuse by non-partner and witnessing violence in childhood. [16] The findings support the assertions of violence associated with women's prior/additional abuse and men's harmful masculinity expression [16] Wandera et al, [43]…”
Section: Study Outcome Variable Explanatory Variablessupporting
confidence: 73%
“…For verbal insult, 20.1% (203/480) and 27.5% (277/480) reported shouting and yelling, respectively. Once more, 251 (24.9%) and 270 (26.8%) women said they experienced divorce threats and second marriage threats, respectively [42] Vyas and Jansen, [16] Almost 40% of women in this sample reported that they had experienced physical or sexual violence through an intimate partner in their life and past-year prevalence was 33% [16] Wandera et al, [43] Significant predictors of current MCU (25.3%) among women were: women's reported ability to ask a partner to use a condom, several living children, and wealth index [43] Kwagala et al, [44] The prevalence of skilled birth attendance among rural women, 55%, is lower than the national majority of 58% and the 63% estimate for developing countries [44] Speizer, [17] More than half of women (57%) reported that they have ever experienced physical or sexual violence [17] Murray et al, [45] 45% of children cited parental fighting as poorly affecting the children and community, and 15% particularly said interpersonal violence (man beating his wife) was a problem for children. 45% of children said dying parents and mourning are complicated, and 25% said that adult alcohol abuse was a big problem cited by children and women [45] The study found a significant relationship between IPV and reported experiences of partner perpetrated reproductive coercion.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These included wealth index, birth cohort, type of place of residence, region of residence, children ever born, currently working and woman earns more than her husband/partner. Education level and religious affiliation were not significant; however, education level and religious affiliation were found to be significant in Uganda among married women (Wandera et al, 2018). Current marital status was not significant, but it was found to be significant in Hong Kong (Wong et al, 2016), and this is central to the main argument behind this study.…”
Section: Multivariate Resultsmentioning
confidence: 62%
“…Tabla 2. Características de las mujeres en edad fértil, en el estudio entre asociación entre el uso de métodos anticonceptivos y violencia doméstica contra la mujer en edad fértil en Perú, ENDES 2017. que no lo hicieron (21) . El hallazgo de estos resultados hace necesario identificar aquellos factores que permitan disminuir esta prevalencia en nuestro país.…”
Section: Discussionunclassified